GENOTYPIC VARIATION, INHERITANCE AND GENETIC ADVANCE IN BREAD WHEAT (Triticum aestivum L.) GENOTYPES IN ETHIOPIA (Applied Biological Research, 2023)
Forty-nine bread wheat (Triticum aestivum L.) genotypes were studied  under rainfed conditions at three agroecologically varied locations in  South-Western Ethiopia namely, Chena, Masha and Shey Bench, during  2017and 2018 with the objective to estimate their genetic variability,  heritability and genetic advance using 7 x 7 simple lattice design. Data  were collected for 12 agronomic characters. The analyses of variance  revealed highly significant differences (p < 0.01) among wheat genotypes  for all the traits studied at these locations, except for the number of t-1 at Chena and biomass yield at Masha wherein  genotypes had significant differences only at p < 0.05 level and the number  of spikelets spike-1 at Shey Bench wherein genotypes showed non significant difference. The phenotypic coefficients of variation were  relatively greater than those of genotypic coefficients of variation for  most of the characters studied; however, the magnitudes of differences  were relatively high for the number of tillers, number of kernels spike-1,  biomass yield and grain yield. High heritability coupled with moderate  genetic advance (as % mean) were observed for days to heading, days to maturity, spike length and grain filling period at all these locations.  Therefore, any improvement in these characters would result in a substantial increment in grain yield in South-Western Ethiopia which,  otherwise, is rich in natural resources but poor in their efficient  utilization.
Keywords: Bread wheat; GCV; genetic advance; heritability; PCV; variability